Effect of intraosseous introduction of selenium/arabinogalactan nanoglycoconjugate on the main indicators of primary metabolism in consolidation of bone fracture - L. V. Rodionova; I. A. Shurygina; L. G. Samoylova; B. G. Sukhov; M. G. Shurygin (Acta Biomedica Scientifica, 2016)
The research was carried out on 9 rabbits (males) of Chinchilla breed with modeling of standard perforating fracture of femoral bone. We performed intraosseous introduction of nanocomposite elemental selenium and heteropolysaccharide arabinogalactan 50 mg Se/kg to individuals of experimental group (n = 3) and NaCl 0,9 % to individuals of control group (n = 6). It was established that local intraosseous introduction of the nanocomposite with perforated fracture model did not affect basal metabolic indicators (body temperature, oxygen consumption, carbon dioxide production), but boosted the metabolic processes in the area of the surgical wound from the 9th to 21st days. It proves the bioavailability of the drug and the possibility of creating a local depot of selenium using a nanocomposite.